2018
DOI: 10.1007/s40430-018-1124-6
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent flow initiation in a horizontal tube: quantitative visualization and CFD analysis

Abstract: The onset of slugging in stratified gas-liquid flow in a 26.4-mm ID horizontal pipe was investigated experimentally using a high-speed digital video processing technique. Spatio-temporal displacement maps were produced to show the evolution of two-phase flow structures (waves, slug precursors and liquid slugs) in the flow entrance region of the air-water mixture flow. The two-phase distribution derived from the visualization technique was in good agreement with measurements performed using non-intrusive capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…They concluded that using the VOF model, the formation and propagation of the slug flow regime along horizontal circular pipes is successfully described and validated against the experimental results. Costa et al [35] worked on a horizontal pipe with an inside diameter of 26 mm using the VOF method. Parameters such as slug velocity and slug length were in good agreement with the experimental results, with relative errors of less than 8% for the slug velocity.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that using the VOF model, the formation and propagation of the slug flow regime along horizontal circular pipes is successfully described and validated against the experimental results. Costa et al [35] worked on a horizontal pipe with an inside diameter of 26 mm using the VOF method. Parameters such as slug velocity and slug length were in good agreement with the experimental results, with relative errors of less than 8% for the slug velocity.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of them were focused on accurately determining film thickness, phase fractions and/or intermittent flow parameters (e.g., slug velocity, frequency and size) in adiabatic (air-water) flows [4,5]. Comparisons against more established experimental techniques [6,7] and numerical simulations have been carried out [8]. Among the most widely investigated methods, one can cite edge detection, watershed segmentation [9], ensemble averaging [10] and "blob" extraction [11].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies [5][6][7] have been conducted in attempt to explore the transient interactions between phases in two-phase flows. A more detailed study investigated the evolution of slug and churn gas pockets using a multivariate pseudo Wigner distribution together with multivariate multiscale entropy to analysis the measured data [5].…”
Section: Introductionmentioning
confidence: 99%